Diagnóstico del consumo de energía eléctrica en el proceso de destilación de agua en los laboratorios de Ciencias de la Vida de la Universidad Politécnica Salesiana, Sede Quito, Campus Girón, durante el año 2014. Implementación de un destilador solar térmico. - Quitiaquez Sarzosa, William Giovanny (2015)
To reduce environmental pollution in the world is necessary to look for renewable energy that is why; this research is focused in the solar power as a clean energy source, because solar energy that we receive from the sun can be transformed and used into electrical energy and thermal energy. For instance, to obtain electrical energy we can use solar panels, and to obtain thermal energy we can use solar stills. The purpose of this investigation is to implement a machine that produces distilled water taking into account the benefits of the sun. This project will be implemented at Salesian University, campus Giron in the Research and Valuation Center of Biodiversity. Therefore, this project will use scientific method, because it will be show how to replace the electrical energy by solar energy and also to determine the energy consumption in the water distillation process using electric energy and solar energy, which is demonstrated by the first law of thermodynamics. To recap, the investment in order to get this kind of machine at Salesian University will get more information about the energy that is used by the water stills GFL 2004 and will provide it a significant save of money in the electrical bill and at the same time it will contribute with the environment care.